The glory of the atonement biblical, historical and practical perspectives : essays in honor of Roger Nicole - Hill, Charles Evan, 1956-; James, Frank A., III (Downers Grove, IL IVP, 2004)
Includes bibliographical references and indexes.
Keywords: Nicole, Roger R; Atonement